2021
DOI: 10.1002/chem.202101742
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the π‐Accepting Properties of Mesoionic Carbenes: A Combined Computational and Experimental Study

Abstract: Mesoionic imidazolylidenes are recognized as excellent electron‐donating ligands in organometallic and main group chemistry. However, these carbene ligands typically show poor π‐accepting properties. A computational analysis of 71 mesoionic imidazolylidenes that bear different aryl or heteroaryl substituents in C2 position was performed. The study has revealed that a diphenyltriazinyl (Dpt) substituent renders the corresponding carbene particularly π‐acidic. The computational results could be corroborated expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 76 publications
(199 reference statements)
1
8
0
4
Order By: Relevance
“…Almost two decades after the first report of an abnormal 5-imidazolinylidene carbene complex, mesoionic carbenes have been developed into a distinguished ligand class. , Among them, 1,2,3-triazole derived mesoionic carbenes, namely 1,2,3-triazolinylidenes, stand out by their modular synthesis via the copper-catalyzed [3 + 2] cycloaddition between azides and alkynes. After their initial reporting by Albrecht et al , they quickly became prominent synthetic targets for (electro-)catalysis, supramolecular chemistry, magnetism, and photochemistry due to their versatile synthesis and comparatively straightforward handling. Throughout these studies, a great effort has been made to decipher their electronic structure. Mesoionic carbenes are commonly believed to be strong σ-donor ligands paralleling heteroaryls; however, recent reports emphasize their π-accepting properties as demonstrated by the isolation of a reduced triazolinylidene ligand . Nevertheless, most studies targeted hitherto late transition metals or main group elements, while early transition-metal complexes with mesoionic carbenes have been rarely explored. Arguably, this can be attributed to the relatively weak bond between N -heterocyclic carbenes and early transition metals .…”
Section: Introductionmentioning
confidence: 99%
“…Almost two decades after the first report of an abnormal 5-imidazolinylidene carbene complex, mesoionic carbenes have been developed into a distinguished ligand class. , Among them, 1,2,3-triazole derived mesoionic carbenes, namely 1,2,3-triazolinylidenes, stand out by their modular synthesis via the copper-catalyzed [3 + 2] cycloaddition between azides and alkynes. After their initial reporting by Albrecht et al , they quickly became prominent synthetic targets for (electro-)catalysis, supramolecular chemistry, magnetism, and photochemistry due to their versatile synthesis and comparatively straightforward handling. Throughout these studies, a great effort has been made to decipher their electronic structure. Mesoionic carbenes are commonly believed to be strong σ-donor ligands paralleling heteroaryls; however, recent reports emphasize their π-accepting properties as demonstrated by the isolation of a reduced triazolinylidene ligand . Nevertheless, most studies targeted hitherto late transition metals or main group elements, while early transition-metal complexes with mesoionic carbenes have been rarely explored. Arguably, this can be attributed to the relatively weak bond between N -heterocyclic carbenes and early transition metals .…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that deprotonation of imidazolium salt 1 (Scheme 1) with a diphenyltriazinyl (Dpt) substituent at C2‐position gave a π‐acidic mesoionic carbene ligand [8] . In the course of our investigations, we found that 1 could be used as precursor to prepare the mesoionic diselenolene ligand 2 .…”
Section: Resultsmentioning
confidence: 72%
“…We recently reported that deprotonation of imidazolium salt 1 (Scheme 1) with a diphenyltriazinyl (Dpt) substituent at C2position gave a π-acidic mesoionic carbene ligand. [8] In the course of our investigations, we found that 1 could be used as precursor to prepare the mesoionic diselenolene ligand 2. The reaction of two equivalents of potassium tert-butoxide (tBuOK) with imidazolium salt 1 in THF at À 40 °C, followed by addition of excess elemental selenium, [9] resulted in the formation of 2, which could be isolated in the form of a purple solid in 90 % yield (Scheme 1).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations